Doświadczenie przemocy w trakcie deportacji: Przypadek Meksykanów ,,wydalonych” ze Stanów Zjednoczonych Ameryki - Agnieszka Radziwinowiczówna (University of Warsaw, Centre of Migration Research (CMR), 2016)
– According to Saskia Sassen (2012), contemporary borders are not erected against other sovereigns, but against nonstate transnational actors, migrants among them. The autonomy of migration of the latter is an act of resistance against the border regimes. Border and immigration controls aim at detecting and disciplining individuals, whose mobility questions state sovereignty. As Walters (2002) and De Genova (2010) notice, deportation and their sheer possibility, or deportability of migrants, produce sovereignty in the face of uncontrolled border-crossings, perceived by the states as a disturbing symptom of 'losing control.' The paper dialectically joins the theories concerning the macrolevel (state sovereignty, capitalist system relying on the immigrant labor force) and the level micro (the individual experience of deportation). The author presents the types of violence they experienced throughout the process of deportation. The analyzed ethnographic material is an outcome of the fieldwork conducted between 2012 and 2014 in the pueblo San Ángel in Lower Mixteca in the Mexican state of Oaxaca. Qualitative interviews with 27 inhabitants of pueblo who were deported from the US between 2006 and 2012 are the basis of the analysis. Deportation was an experience of the US state for this women and men who attempted to remain 'in the shadows.' The article presents the analysis of the phases of deportation (detection, detention, immigration court, transfer and return to Mexico) and the types of violence experienced. It is necessary to include also types of violence other than the physical, among them the objective types of violence: (éZiézek 2010): the structural (Galtung 1969) and the symbolic (Bourdieu, Wacquant 2001). The author demonstrates that symbolic violence can lead to resigning from appealing against the deportation order. The author describes how violence used against migrants reconstructs the US sovereignty in lieu of 'the shadows' where the migrants lived.
Keywords: 330; violence; sovereignty; migrations; deportation; Mexico; United States of America